The Development of VBA Powerpoint-Assisted Learning Media to Improve Students’ Cognitive Ability - Kasiaradja, Charisa S; Zakaria, Perry; Oroh, Franky Alfrits (IKIP Siliwangi, 2025)
The Education plays a crucial role in developing cognitive skills, including critical thinking and problem-solving, which are essential for student learning and future competitiveness. However, many students in Indonesia face difficulties in understanding mathematics, particularly on topics such as ratios, due to the limited use of interactive learning media. This study aims to develop an interactive learning media using Visual Basic Application (VBA) for PowerPoint and to evaluate its validity and practicality. The development followed the ADDIE model, which includes five stages: analysis, design, development, implementation, and evaluation. Validation was conducted to assess both media and content quality, while practicality was measured through responses from students and teachers. Data were collected using validation sheets, questionnaires, and scoring rubrics, and analyzed quantitatively to determine validity and practicality categories. The results showed that the learning media obtained an average score of 3.09 for media validity and 3.47 for content validity, both categorized as “very valid.” Student responses reached a score of 740 out of 800, while teacher responses achieved a perfect score of 40 out of 40, indicating that the media is highly practical. Based on these findings, it can be concluded that VBA-based PowerPoint learning media is valid, practical, and effective in enhancing cognitive engagement and supporting mathematics learning, particularly on the topic of ratios.